Microbiological Evaluation of an Active Tubotympanic Type of Chronic Suppurative Otitis Media - Srivastava, A; Singh, RK; Varshney, S; Gupta, P; Bist, SS; Bhagat, S; Gupta, N (Nepalese Journal of ENT Head and Neck Surgery, 2011)
Keywords: Antibiotics; chronic otitis media; microbiology DOI: 10.3126/njenthns.v1i2.4758 Nepalese J ENT Head Neck Surg Vol.1 No.2 (2010) p.14-16